Upaya Peningkatan Kesejahteraan Ekonomi Masyarakat Desa melalui Industri Rumahan Gerabah, Studi Kasus di Desa Maregam Kecamatan Tidore Selatan, Kota Tidore Kepulauan - Hamisi, Nuria; HS, Nur Azizah; Radjaloa, Vhyda Hamidah Aulia (Jurnal Ilmiah Wahana Pendidikan, 2024)
Maregam is one of the villages in North Maluku where the people have creativity as craftsmen using soil, the local people call it "boso" (pottery). Pottery is a handicraft made from clay. The process of making pottery in Maregam village has long been developed by the community, starting from the story of a woman named Mo're who lived in ancient times (Ngongole), namely an era before humans knew about metal, so they used stone and earth as the main materials for making tools. At that time, "Mo're" made pottery as an alternative tool used to support kitchen utensils, because at that time there were no tools that could be used by the community to support their living needs. The aim of this research is to determine the efforts made by pottery craftsmen to improve the economic welfare of the community in Maregam Village, South Tidore District, Tidore City, Islands, North Maluku Province. Tidore City, Islands, North Maluku Province. This research methodology uses a qualitative descriptive research method with a phenomenological approach, a qualitative descriptive method is a method that aims to systematically describe a situation, the condition of the object in the field of study at one time accurately. The results of the research are increasing capital, increasing product innovation, expanding marketing networks, and business prosperity.